2021
DOI: 10.1007/s11628-021-00445-w
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the perceived satisfaction and revisiting intentions of lodgers in a restricted service scenario: evidence from the hotel industry in quarantine

Abstract: The strict contactless management measures that have been implemented to control the spread of the COVID-19 pandemic have severely limited the ability of hotel staff to provide guest services in a quarantine scenario. This study examines the effect of lodgers' perceptions of the services provided in hotels under quarantine on their satisfaction and intentions to revisit. A self-administered questionnaire was distributed to 250 interviewees who had experienced lodging in quarantined hotel in Mainland China and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 143 publications
(177 reference statements)
0
13
0
Order By: Relevance
“…The role of a hotel is no longer limited to providing overnight stays for travellers, as many hotels have been converted to quarantine facilities during the COVID-19 pandemic. To respond to the fact that guests' quarantine experience is unforgettable but ambiguous (Wang et al, 2021), this research has identified and categorised the memorable quarantel experiences of Chinese student returnees into six themes (i.e. staff, room, hygiene and disinfection, food, healthcare and location) encompassing 20 underlying attributes (see Table 3), which include both positive and negative experience.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The role of a hotel is no longer limited to providing overnight stays for travellers, as many hotels have been converted to quarantine facilities during the COVID-19 pandemic. To respond to the fact that guests' quarantine experience is unforgettable but ambiguous (Wang et al, 2021), this research has identified and categorised the memorable quarantel experiences of Chinese student returnees into six themes (i.e. staff, room, hygiene and disinfection, food, healthcare and location) encompassing 20 underlying attributes (see Table 3), which include both positive and negative experience.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Baby Boomers prefer good interior room design, cleanliness, and good staff attitude (Patterson et al, 2017). Recently, Wang et al (2021) pointed out that a positive memorable experience will increase guests’ satisfaction, resulting in high revisit intention when quarantels have reverted to the normal hotel after the pandemic. Therefore, this research provides a good opportunity to explore the memorable experiences in a very specialised type of hotel – quarantel – from the student perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Events as COVID-19 evidently impact the competitive edge of firms and the service that they were used to provide (e.g., McKinsey 2021 ; Wang et al 2021 ). Due to the COVID-19 pandemic, governments have forced many social spaces to rapidly adjust their spaces in line with regulations that stimulate social distancing, implying less people being physically present.…”
Section: Literature Reviewmentioning
confidence: 99%